2011
DOI: 10.1080/09583157.2011.580836
|View full text |Cite
|
Sign up to set email alerts
|

Life history and demography ofPsyllaephagus zdeneki(Hymenoptera: Encyrtidae), a potential candidate for biological control of olive psylla,Euphyllura pakistanica(Hemiptera: Psyllidae)

Abstract: Life history and demographic parameters of Psyllaephagus zdeneki Noyes and Fallahzadeh (Hymenoptera: Encyrtidae) were studied on its host the olive psyllid, Euphyllura pakistanica Loginova (Hemiptera: Psyllidae). Experiments were conducted in a growth chamber at 20918C, relative humidity of 6095%, and a photoperiod of 16:8 (L: D) hours. Four different olive cultivars (Fishomi, Shenge, Oil and Yellow) were used to test possible host plant influence on parasitoid performance. The pre-imaginal developmental perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…They pointed out the determining role of botanical and pomological characteristics, volatile chemical compounds in the fruit, as well as agronomic factors such as plowing and fertilizing in the sensitivity and resistance of olive cultivars to olive fruit y. Asadi et al (2011) determined the development, reproduction, and growth population parameters of the olive psyllid, Euphyllura pakistanica Loginova (Hemiptera; Psyllidae) on four olive cultivars; Fishomi, Roghani, Zard, and Shengeh under controlled laboratory conditions. Their ndings showed that the development and demographic parameters of olive psyllid E. pakistanica were in uenced by cultivars variety.…”
Section: Introductionmentioning
confidence: 99%
“…They pointed out the determining role of botanical and pomological characteristics, volatile chemical compounds in the fruit, as well as agronomic factors such as plowing and fertilizing in the sensitivity and resistance of olive cultivars to olive fruit y. Asadi et al (2011) determined the development, reproduction, and growth population parameters of the olive psyllid, Euphyllura pakistanica Loginova (Hemiptera; Psyllidae) on four olive cultivars; Fishomi, Roghani, Zard, and Shengeh under controlled laboratory conditions. Their ndings showed that the development and demographic parameters of olive psyllid E. pakistanica were in uenced by cultivars variety.…”
Section: Introductionmentioning
confidence: 99%
“…The pest produces large amounts of honeydew which absorb dust and microorganisms, thus preventing photosynthesis (Porkhosravani et al 2020;Sheibani and Hassani 2014). Chemical control is used more than other methods that addition to the high costs, effect on environment, human health and natural enemies (Asadi et al 2009); therefore, it must be replaced with another approach such as integrated and ecological controls. A. pistaciae could be found in locations with an altitude range of 900-2150 m throughout the country (Ahmadi et al 2013) and nearly everywhere the pistachio trees are found.…”
Section: Introductionmentioning
confidence: 99%